2012
DOI: 10.5812/aapm.4092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Effect of Lidocaine, Morphine and Ketamine Spray on Post-Tonsillectomy Pain in Children

Abstract: BackgroundAn effective pain therapy to block or modify the physiological responses to stress has become an essential component of modern pediatric anesthesia and surgical practice.ObjectivesThe goal of this study was to compare the analgesic effects of the spray forms of; lidocaine, morphine, ketamine, and normal saline on post-tonsillectomy pain scores in children.Patients and MethodsA total of 120 children, American Society of Anesthesiologist (ASA) class I–II, scheduled for elective tonsillectomy were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 16 publications
(16 reference statements)
3
30
0
Order By: Relevance
“…Propofol in combination with midazolam can be titrated to achieve a moderate level of anesthesia in colonoscopy, but it is important to note that this combination lacks analgesic properties and may result in the sensation of more pain and consequently a low level of patient satisfaction (17). The mean of procedure duration was similar in patients of both groups (21 versus 23 minutes) in this study, similar to Sipe and Paspatis’studies (15, 16). The frequency of nausea in patients who were sedated with propofol plus narcotics in the Kostash et al study was 26 %, (range 16-40%) while it was much less (12.5%) in our study (18).…”
Section: Discussionsupporting
confidence: 90%
“…Propofol in combination with midazolam can be titrated to achieve a moderate level of anesthesia in colonoscopy, but it is important to note that this combination lacks analgesic properties and may result in the sensation of more pain and consequently a low level of patient satisfaction (17). The mean of procedure duration was similar in patients of both groups (21 versus 23 minutes) in this study, similar to Sipe and Paspatis’studies (15, 16). The frequency of nausea in patients who were sedated with propofol plus narcotics in the Kostash et al study was 26 %, (range 16-40%) while it was much less (12.5%) in our study (18).…”
Section: Discussionsupporting
confidence: 90%
“…FLACC pain scale was evaluated during recovery period. The results showed that lidocaine spray had the best pain controlling effect in the early recovery, but after 40 minutes, ketamine and morphine sprays were more effective than lidocaine spray (8). In our study, post-operative pain in rectal acetaminophen group was less than IV acetaminophen group.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the efficacy of lidocaine, morphine, and ketamine spray were compared (8, 9). Efficacy of honey on post-tonsillectomy pain has also been investigated (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal analgesia is a new approach that uses different drugs and techniques to reduce the total dose of any one drug, which reduces the risk of side effects (2). Opioids are the cornerstone of postoperative pain control, but the combination of nonopioid analgesics, such as acetaminophen, nonsteroidal anti-inflammatory drugs, and ketamine, with opioids provides an analgesic-sparing effect and decreases side effects (3, 4).…”
Section: Introductionmentioning
confidence: 99%